Customer relationship management as a mediator of digital empowerment and entrepreneurial success: A socio-economic perspective on women entrepreneurs in Malaysia - Wan Chek , Wan Izzah Zahirah; Ishak , Noormaizatul Akmar; Othman , Abdul Azim; Baharin , Ahmad Tajudin; Alshamesti, Omar; Osman , Mohd Fisol (Journal of Islamic, Social, Economics and Development, 2025)
This study examines the mediating role of Customer Relationship Management (CRM) in the relationship between digital empowerment and entrepreneurial success among women entrepreneurs in Malaysia. Drawing on the Resource-Based View (RBV) theory, CRM is conceptualized as an intangible resource that integrates technological capability with relationship-oriented values such as trust (amanah), excellence (ihsan), and social responsibility (muamalat) within an Islamic economic framework. Using a quantitative approach, data were collected from 200 Malaysian women entrepreneurs operating within the gig and digital economy sectors. Partial Least Squares–Structural Equation Modeling (PLS-SEM) was employed to test the proposed relationships. Findings reveal that digital empowerment significantly influences CRM practices, and CRM, in turn, enhances entrepreneurial success while partially mediating the relationship between empowerment and success. The results underscore CRM’s dual function as a technological enabler and ethical bridge for sustainable entrepreneurship. This study contributes to socio-economic development literature by aligning CRM-based empowerment with Malaysia’s MyDigital Blueprint 2030 and the Sustainable Development Goals (SDG 5 – Gender Equality and SDG 8 – Decent Work and Economic Growth).